Toward a more general approach to political stability in comparative political systems - Thomas Apolte (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2012)
This paper provides a general framework for analyzing political (in)stability in comparative political systems. It distinguishes different subgroups of a society, some of which have a potential for pursuing a redistribution of wealth in its broadest sense via constitutional or non-constitutional government overturns. Political instability implies a cycle of overturns and redistributions with no stable equilibrium. It will be shown that individual incentives for participating in overturn attempts hinge not upon specific distributions of wealth but are rather dependent on the respective structure and credibility of promises and threats within and across the different subgroups of the society. What is more, without credible commitments of the incumbent governments to a carrot-and-stick policy there will be the danger of endless over-turn and redistribution cycles, leading to failed states. For much the same reason, democratic constitutions contain effective measures against redistribution cycles. Stability within non-democracies, by contrast, can be explained by the fact that commitments among potential re-bels cannot be backed by formal institutions, whereas incumbent governments can use their legal surrounding for developing institutions that, in turn, help them to embed potentially threatening societal groups into a system of carrot and stick.
Keywords: D72; D74; O15; P16; 330; political economy; revolutions; credible commitments